Lanczos steps to improve variational wave functions. (September 2015) - Becca, Federico; Hu, Wen-Jun; Iqbal, Yasir; Parola, Alberto; Poilblanc, Didier; Sorella, Sandro
Abstract: Gutzwiller-projected fermionic states can be efficiently implemented within quantum Monte Carlo calculations to define extremely accurate variational wave functions for Heisenberg models on frustrated two-dimensional lattices, not only for the ground state but also for low-energy excitations. The application of few Lanczos steps on top of these states further improves their accuracy, allowing calculations on large clusters. In addition, by computing both the energy and its variance, it is possible to obtain reliable estimations of exact results. Here, we report the cases of the frustrated Heisenberg models on square and Kagome lattices.